Bio-organic fertilizers modulate the rhizosphere bacterial community to improve plant yield in reclaimed soil - Qiao, Cece; Yang, Jing; Shao, Qingqin; Fu, Jingli; Zheng, Xueyun; Zhao, Jianrong; Ren, Lantian; Wu, Wenge; Wang, Jianfei (Frontiers in Plant Science, 2025)
Soil reclamation is a crucial strategy for restoring degraded land and improving agricultural productivity, yet the underlying microbiological mechanisms that drive soil quality improvement remain inadequately understood. To address this, a rice field experiment under chemical fertilizer (CF), organic fertilizer (OF), and B. subtilis-enriched bio-organic fertilizer (BOF) was conducted to assess the impact of different fertilization treatments on rhizosphere soil bacterial community by targeted sequencing in reclaimed paddy soil. The results revealed that BOF significantly enhanced rice yield and improved soil attributes, including a reduction in soil pH and an increase in microbial diversity. Compared with the CF and OF, BOF exhibited a more pronounced effect on the enrichment of indigenous Bosea spp. in the rhizosphere. Metabolomic analysis further revealed that the relative abundance of Bosea was positively associated with increased levels of aromatic compounds such as benzoic acid and tropolone, which are potentially linked to improved soil functionality. These findings suggest that the synergistic interaction between B. subtilis and native Bosea populations may enhance soil health and promote sustainable crop productivity by altering microbial community structure and activating beneficial metabolic pathways. Collectively, this study provides further insight into the role of bio-organic fertilizers in promoting ecological restoration and sustainable agriculture in reclaimed soils.